STUDY ON THE RECOVERY OF THE ANKLE SPRAINS OF THE ATHLETES - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The recovery of the athletes with ankle sprain is essential for physical therapy program to relieve pain, for mechanical protection of the ankle joint, to recover the normal gait and for socio-professional integration of the athlete. The purpose of this study is to find ways of applying early and systematically the kinesiology methods and procedures by which we can restore as much and faster functional capacity of the leg.